On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda: Palaemonidae) - Park, J; Grave, S; Kim, W (Magnolia Press, 2019)
The palaemonid genus Isopericlimenaeus is currently comprised of only the type species, Isopericlimenaeus gorgonidarum, with the diagnostic character of the genus being the presence of a molar and fossa structure on both second chelipeds. Periclimenaeus uropodialis is a closely related species, which has either been considered a synonym of I. gorgonidarum or placed as a valid species in the related genus, Periclimenaeus. During fieldwork in the Philippines, Taiwan and Korea, several species of Periclimenaeus and other sponge associated shrimps belonging to the family Palaemonidae were collected, including I. gorgonidarum and P. uropodialis. Based on a morphological and molecular comparison, it is demonstrated that both taxa are conspecific and that Isopericlimenaeus is a junior synonym of Periclimenaeus.